Uptake of a Cervical Cancer Clinical Decision Support Tool: A Mixed-Methods Study - Huguet, Nathalie; Ezekiel-Herrera, David; Gunn, Rose; Pierce, Alison; O'Malley, Jean; Jones, Matthew; Marino, Miguel; Gold, Rachel (Applied Clinical Informatics, 2023)
Objectives Clinical decision support (CDS) tools that provide point-of-care reminders of patients' care needs may improve rates of guideline-concordant cervical cancer screening. However, uptake of such electronic health record (EHR)-based tools in primary care practices is often low. This study describes the frequency of factors associated with, and barriers and facilitators to adoption of a cervical cancer screening CDS tool (CC-tool) implemented in a network of community health centers.Methods This mixed-methods sequential explanatory study reports on CC-tool use among 480 community-based clinics, located across 18 states. Adoption of the CC-tool was measured as any instance of tool use (i.e., entry of cervical cancer screening results or follow-up plan) and as monthly tool use rates from November 1, 2018 (tool release date) to December 31, 2020. Adjusted odds and rates of tool use were evaluated using logistic and negative-binomial regression. Feedback from nine clinic staff representing six clinics during user-centered design sessions and semi-structured interviews with eight clinic staff from two additional clinics were conducted to assess barriers and facilitators to tool adoption.Results The CC-tool was used ≥1 time in 41% of study clinics during the analysis period. Clinics that ever used the tool and those with greater monthly tool use had, on average, more encounters, more patients from households at >138% federal poverty level, fewer pediatric encounters, higher up-to-date cervical cancer screening rates, and higher rates of abnormal cervical cancer screening results. Qualitative data indicated barriers to tool adoption, including lack of knowledge of the tool's existence, understanding of its functionalities, and training on its use.Conclusion Without effective systems for informing users about new EHR functions, new or updated EHR tools are unlikely to be widely adopted, reducing their potential to improve health care quality and outcomes.
Keywords: clinical decision support; community health centers; cervical cancer screening; mixed methods